For Better and for Worse? On the Transformation of the Finnish Social Assistance Scheme - Helena Blomberg; Christian Kroll (Social Work and Society, 2020)
The recent reform of Finnish social assistance may be described as, in many ways, going against the European tide toward a welfare service state. The reform involved the transfer of the implementation of social assistance from municipal frontline workers within social services to national frontline workers working for the Social Insurance Institution of Finland. Thus, it was felt that a"mere" change of administration would result, among other things, in less stigma and arbitrariness and a strengthening of the social transfer character of the assistance. This paper analyses the consequences of the reform from different angles by utilizing previously identified ideational frames for the reform. Against the background of these frames, we highlight the outcomes of the reform from the perspectives of the system, client and front-line workers. We conclude that this"purely" administrative reform seems to have created a more visible division between social assistance recipients, a kind of 'upstairs and downstairs,' even among those with the most limited financial resources.